Mobile health to promote physical activity in people post stroke or transient ischemic attack - study protocol for a feasibility randomised controlled trial - Thurston, Charlotte (2023)
Background: Physical activity is essential to improve health and reduce the risk of recurrence of stroke or transient ischemic attack (TIA). Still, people post stroke or TIA are often physically inactive and the availability of physical activity promotion services are often limited. This study builds on an existing Australian telehealth-delivered programme (i-REBOUND– Let’s get moving) which provides support for home-based physical activity for people post stroke or TIA. The aim of this study is to test the feasibility, acceptability, and preliminary effects of a mobile Health (mHealth) version of the i-REBOUND programme for the promotion of physical activity in people post stroke or TIA living in Sweden. Methods: One hundred and twenty participants with stroke or TIA will be recruited via advertisement. A parallel-group feasibility randomised controlled trial design with a 1:1 allocation ratio to 1) i-REBOUND programme receiving physical exercise and support for sustained engagement in physical activity through behavioural change techniques, or 2) behavioural change techniques for physical activity. Both interventions will proceed for six months and be delivered digitally through a mobile app. The feasibility outcomes (i.e., reach, adherence, safety and fidelity) will be monitored throughout the study. Acceptability will be assessed using the Telehealth Usability Questionnaire and further explored through qualitative interviews with a subset of both study participants and the physiotherapists delivering the intervention. Clinical outcomes on preliminary effects of the intervention will include blood pressure, engagement in physical activity, self-perceived exercise self-efficacy, fatigue, depression, anxiety, stress and health-related quality of life and will be measured at baseline and at 3, 6 and 12 months after the baseline assessments. Discussion: We hypothesise that the mHealth delivery of the i-REBOUND programme will be feasible and acceptable in people post stroke/TIA living in rural and urban regions of Sweden. The results of this feasibility trial will inform the development of full-scale and appropriately powered trial to test the effects and costs of mHealth delivered physical activity for people after stroke or TIA.